2003
DOI: 10.1074/jbc.m302704200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation at Serine 75 Is Required for UV-mediated Degradation of Human Cdc25A Phosphatase at the S-phase Checkpoint

Abstract: The human Cdc25A phosphatase plays a pivotal role at the G 1 /S transition by activating cyclin E and A/Cdk2 complexes through dephosphorylation. In response to ionizing radiation, Cdc25A is phosphorylated by both Chk1 and Chk2 on Ser-123. This in turn leads to ubiquitylation and rapid degradation of Cdc25A by the proteasome resulting in cell cycle arrest. We found that in response to UV irradiation, Cdc25A is phosphorylated at a different serine residue, Ser-75. Significantly, Cdc25A mutants carrying alanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 21 publications
7
69
1
1
Order By: Relevance
“…This phosphorylation is required for Chk1-induced degradation of Cdc25A and primes Cdc25A for degradation both in a normal cell cycle and in response to DNA damage. Indeed, the homologous serine in human Cdc25A (Ser 76) was found by Hassepass et al (2003) to be a Chk1 phosphorylation site in vitro. The same group demonstrated that Ser 76 mediates Cdc25A stabilization in response to UV-induced DNA damage.…”
Section: Cdc25a and Checkpointsmentioning
confidence: 99%
“…This phosphorylation is required for Chk1-induced degradation of Cdc25A and primes Cdc25A for degradation both in a normal cell cycle and in response to DNA damage. Indeed, the homologous serine in human Cdc25A (Ser 76) was found by Hassepass et al (2003) to be a Chk1 phosphorylation site in vitro. The same group demonstrated that Ser 76 mediates Cdc25A stabilization in response to UV-induced DNA damage.…”
Section: Cdc25a and Checkpointsmentioning
confidence: 99%
“…Loss-Chk1-mediated Cdc25A phosphorylation leads to Cdc25A proteolytic destruction, thereby blocking cell cycle progression (24,27,(65)(66)(67). To explore whether 17-AAG-induced Chk1 loss affects Cdc25A destruction, we treated HeLa cells with 17-AAG for 1 h and then with gemcitabine for an additional 4 h and examined Cdc25A levels (Fig.…”
Section: -Aag-mediated Chk1 Loss Blocks Cdc25amentioning
confidence: 99%
“…During the S phase, SCF ␤-TRCP regulates Cdc25A degradation in an unperturbed cell division cycle and in response to DNA damage, requiring phosphorylation of serines 76, 79, 82, and 85 (13)(14)(15). The Cdc25A destruction induced by ionizing and UV irradiation requires the phosphorylation of Ser-123 mediated by the ATM/Chk2 or ATR/Chk1 pathway (7,16,17) and the phosphorylation of Ser-76, respectively (18,19). Rapid Cdc25A degradation in response to DNA damage is a part of the DNA damage checkpoint mechanism that protects genomic integrity by arresting the cell cycle progression and allowing cells to repair damaged DNA.…”
mentioning
confidence: 99%